Associations between individual and collective efficacy beliefs and students' bystander behavior. Issue 11 (17th June 2020) - Sjögren, Björn; Thornberg, Robert; Wänström, Linda; Gini, Gianluca
Abstract: This study examined whether defending and passive bystanding during peer victimization episodes were associated with individual‐ and classroom‐level efficacy to stop peer victimization. Self‐report survey data were analyzed from 1, 467 Swedish fourth‐grade students (mean age = 10.55) from 100 classrooms in 63 schools. Multilevel analyses revealed that, when witnessing peer victimization, students more often defended victims if they were high in defender self‐efficacy and if they belonged to classrooms high in collective efficacy. In contrast, students were more likely to remain passive if they were low in defender self‐efficacy and if they belonged to classrooms low in collective efficacy. Taken together, our findings suggest that efficacy beliefs both at the individual and at the classroom level contribute to explaining variability in students' bystander behaviors, which has potential implications for prevention and intervention work.